Наукові засади формування якості плодових тіл їстівних грибів родів PLEUROTUS, CYCLOCYBE, FLAMMULINA ТА CALOCYBE: Дисертація… д-ра с.-г. наук - Бандура, Ірина Іванівна; Bandyra, Iryna (My University, 2023)
UKR: Кваліфікаційна наукова праця присвячена обґрунтуванню наукових засад формування якості врожаю ксилотрофних видів грибів з доведеною харчовою та лікарською цінністю: гливи звичайної, гливи легеневої, гливи степової, гливи лимонношапинкової або золотої, опенька зимового, опенька тополевого та тропічного виду - калоцибе індійського. У роботі досліджено технологічні складові процесу культивування означених видів, які дозволяють отримувати плодові тіла з прогнозованими квалітативними характеристиками відповідно до вимог післязбиральних процедур. Було проведено комплексний скринінг 24 культиварів P. ostreatus (5 штамів), P. pulmonarius (1), P. eryngii (3), P. citrinopileatus (1), F.velutipes (10), C. aegerita (3), С. indica (1) в умовах промислових виробництв, за результатами якого визначено технічні характеристики продуктивності, параметри фенотипічних ознак, біохімічний склад плодових тіл, коефіцієнти виходу напівфабрикатів у післязбиральних операціях і первинної переробки, що дає змогу відібрати найбільш перспективні для промислового впровадження штами. Доведено необхідність досягнення елективності субстратів за рахунок збалансування складу органогенних та ессенціальних елементів, елімінації патогенних мікроорганізмів та створення певної структури субстратів, як найважливішого фактору формування якості врожаю ксилотрофних видів. Визначено індивідуальні потреби досліджених культиварів до ступеня елективності субстратів, їх біологічну ефективність та характер змін біохімічного складу отриманого врожаю відповідно до складу субстратних композицій.\\\\\\\\\\\\\\\\\ ENG: The qualitative scientific work is substantiated scientific bases for formation the quality of xylotrophic mushroom species with proved food and medicinal value: oyster mushroom, lung mushroom, king oyster mushroom, lemon or gold oyster mushroom, winter needle mushroom, poplar mushroom or “piopinno” and tropical exotic species “milky mushroom”. In this work, the technological components of the cultivation process of the above species were investigated to obtain fruiting bodies with predictable qualitative characteristics by the requirements of post-harvest procedures. A comprehensive screening of 24 strains: P. ostreatus (5 strains), P. pulmonarius (1), P. eryngii (3), P. citrinopileatus (1), F. velutipes (10), C. aegerita (3), C. indica (1) under industrial production conditions, based on the results of which technical characteristics of productivity, parameters of phenotypic traits, biochemical contains of fruiting bodies, yield ratios of semi products in postharvest operations and primary processing were determined, allowing selection of the most promising strains for industrial implementation. The necessity of achieving substrate selectivity by balancing the composition of organogenic, and essential elements, elimination of pathogenic microorganisms and creating a certain structure of substrates as the most crucial factor in the formation of yield quality of xylotrophic species is proven. The individual requirements of the studied cultivars for the degree of substrate electivity, their biological efficacy, and the nature of changes in the biochemical composition of the yield obtained in accordance with the composition of substrate compositions were determined. The possibility of predicting the quality phenotypic and biochemical characteristics of cultivars through the necessary technical operations has been revealed: making substrate units of the required mass, forming the fruiting zone through the perforations of a given size, or opening area, spatial position on the shelves, applying the best height of the cover soil, and conducting scratching technic. The results of the analysis of the theoretical basis for the formation of consumer quality xylotrophic mushrooms under the experience of world and local mushroom production are presented in the first chapter. The key issues of creating an effective mushroom production system using new crops with interesting phenotypic traits and nutritional characteristics, the quality of spawn and substrates are formulated. The role of microclimatic conditions and microbiological factor and the formation of crop quality is considered. Modern requirements on for storage and features of processing of mushroom raw materials were analysed.
Bandura I.I. Scientific principles of formation culinary mushrooms Pleurotus, Cyclocybe, Flammulina and Calocybe genres quality - Qualifying scientific work on the rights of the manuscript.
Keywords: якість грибів; калоцибе індійський; промислове культивування грибів; глива звичайна; біологічна ефективність; морфологія плодових тіл; опеньок тополевий; моделювання субстратних композицій; опеньок зимовий; глива легенева; глива золота або лимонно-шапинкова; глива степова; mushroom industrial cultivation; quality of mushrooms; biological efficiency; morphology of fruiting bodies; modelling of substrate compositions; oyster mushroom; lung oyster mushroom; king oyster mushroom; gold oyster mushroom; winter mushroom; milky mushroom; poplar mushroom